2016
DOI: 10.3390/axioms5010006
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Production Rate of a One-Dimensional Alpha-Fractional Diffusion Process

Abstract: Abstract:In this paper, the one-dimensional α-fractional diffusion equation is revisited. This equation is a particular case of the time-and space-fractional diffusion equation with the quotient of the orders of the time-and space-fractional derivatives equal to one-half. First, some integral representations of its fundamental solution including the Mellin-Barnes integral representation are derived. Then a series representation and asymptotics of the fundamental solution are discussed. The fundamental solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…To mix the advantages of both space and time fractionality, spacetime double-fractional diffusion has been introduced and extensively studied from the theoretical point of view [15,23,28,29,31,32,39]; however, it has only been recently considered in financial modeling [8,14,24,25,26]. It features a more complete structure than the simple composition of the time and space fractional models as it exhibits non trivial phenomena including larges jumps and memory effects, which can not be understood as a simple market time re-parametrization of an α-stable process.…”
Section: Introductionmentioning
confidence: 99%
“…To mix the advantages of both space and time fractionality, spacetime double-fractional diffusion has been introduced and extensively studied from the theoretical point of view [15,23,28,29,31,32,39]; however, it has only been recently considered in financial modeling [8,14,24,25,26]. It features a more complete structure than the simple composition of the time and space fractional models as it exhibits non trivial phenomena including larges jumps and memory effects, which can not be understood as a simple market time re-parametrization of an α-stable process.…”
Section: Introductionmentioning
confidence: 99%
“…i.e., in the case of the α-fractional diffusion equation that was analyzed in detail in [16][17][18]. Thus the α-fractional diffusion equation can be treated as a "right fractionalization" of the conventional diffusion equation.…”
Section: The Entropy Production Rates Of the Fractional Diffusion Promentioning
confidence: 99%
“…The n-dimensional case of this equation was analyzed in Reference [7]. In Reference [16], it was shown that the entropy production rate of the fundamental solution to the one-dimensional α-fractional diffusion equation is exactly the same as in the case of the conventional diffusion equation. The α-fractional diffusion equation is a PDE with the Caputo time-fractional derivative of order α, 0 < α ≤ 1 and the fractional spatial derivative of order 2α.…”
Section: Introductionmentioning
confidence: 99%
“…τ contains a Gammafunction with the same parameter, namely Γ 1 − s 2 , that could be canceled in their product. This feature is valid only in the two-dimensional case, whereas the Mellin-Barnes integrals of the type (3.14) are essentially more complicated both in the one-and in the three-dimensional cases (see the very recent paper [12] for the results in the one-dimensional case).…”
Section: Fundamental Solution Of the α-Fractional Diffusion Equationmentioning
confidence: 99%
“…Let us mention that the α-fractional diffusion equation is a particular case of the more general time-and space-fractional diffusion equation that has been analyzed in the one-dimensional case in [21] and in the multi-dimensional case in [6] and [29] to mention only few of many relevant publications. In [12], the case of the one-dimensional α-fractional diffusion equation was considered in detail.…”
Section: Introductionmentioning
confidence: 99%